Improving yields by switching central metal ions in porphyrazine-catalyzed oxidation of glucose into value-added organic acids with SnO2 in aqueous solution - Zhang, Quanquan; Li, Xin; Wang, Xingwang; Huang, Xin; Liu, Yuncai; Wu, Fengshou; Zhang, Bingguang; Deng, Kejian (Frontiers in Chemistry, 2023)
Photocatalysis has exhibited huge potential in selective conversion of glucose into value-added chemicals, therefore modulation of photocatalytic material for selective upgrading of glucose is significant. Here, we have investigated the insertion of different central metal ions, -Fe, -Co, -Mn and -Zn, into the porphyrazine loading with SnO2 for access to more efficient transformation of glucose into value-added organic acids in aqueous solution at mild reaction conditions. The best selectivity for organic acids containing glucaric acid, gluconic acid and formic acid of 85.9% at 41.2% glucose conversion was attained by using SnO2/CoPz composite after reacting for 3 h. The effects of central metals on surficial potential and related possible factors have been studies. Experimental results showed that the introduction of metalloporphyrazine with different central metals on the surface of SnO2 has a significant effect on the separation of photogenerated charges and changing the adsorption and desorption of glucose and products on the catalyst surface. The central metal of cobalt and iron contributed more to the positive effects towards enhancing conversion of glucose and yields of products and manganese and zinc contributed more to the negative effects resulted in poor yield of products. The differences from central metals may belong to the surficial potential change of composite and the coordination effects between metal and oxygen atom. Appropriate surficial potential environment of photocatalyst may achieved better interactive relationship between catalyst and reactant while appropriate ability of producing active species matched with adsorption and desorption abilities would gain better yield of products. These results have supplied valued idea for designing more efficient photocatalyst in selective oxidation of glucose utilizing clean solar energy in future.